Electrochemical Generation of Peroxy Radicals and Subsequent Peroxidation of 1,3-Dicarbonyls in an Undivided Cell - Bityukov, Oleg V.; Skokova, Ksenia V.; Vil’, Vera A.; Nikishin, Gennady I.; Terent’ev, Alexander O. (Organic letters, 2024)
The generation of peroxy radicals from hydroperoxides with subsequent selective peroxidation of 1,3-dicarbonyls in an undivided electrochemical cell under constant current conditions is reported. The method provides a variety of peroxy-containing barbituric acids and 4-hydroxy-2(5H)-furanones with yields of up to 74%. Only the combination of anodic and cathodic processes provides efficient peroxidation by generating a set of alkoxy and peroxy radicals. NaNO3 acts as both an electrolyte and a redox mediator of radical reactions.